Thermal stability of a-C:H:SiOx thin films in hydrogen atmosphere; Thin Solid Films; Vol. 690 - Grenaderov A. S. Aleksandr Sergeevich; Soloviev (Solovyev) A. A. Andrey Aleksandrovich; Oskomov K. V. Konstantin Vladimirovich; Sypchenko V. S. Vladimir Sergeevich (2019, 2019)
Title screen